Magnetic moments of the octet, decuplet, low-lying charm, and low-lying bottom baryons in a nuclear medium - Tsushima, K (Progress of theoretical and experimental physics, 2022)
Abstract We study the magnetic moments of the octet, decuplet, low-lying charm, and low-lying bottom baryons with nonzero light quarks in symmetric nuclear matter using the quark–meson coupling (QMC) model, which satisfies the constraint for the allowed maximum change (swelling) of the in-medium nucleon size derived from the y-scaling data for 3He(e, e′) and 56Fe(e, e′). This is the first study to estimate the in-medium magnetic moments of the low-lying charm and bottom baryons with nonzero light quarks. The present QMC model also satisfies the expected allowed maximum enhancement of the nucleon magnetic moments in nuclear matter. Moreover, it has been proven that the calculated in-medium to free proton electromagnetic form factor (EMFF) ratios calculated within the QMC model reproduce well the proton EMFF super ratio extracted from $^4{\rm He}(\vec{e},e^{′ }\vec{p})^3{\rm H}$ at Jefferson Laboratory. The medium modifications of the magnetic moments are estimated by evaluating the in-medium to free space baryon magnetic moment ratios to compensate the MIT bag deficiency to describe the free space octet baryon magnetic moments, where ratios are often measured directly in experiments even without knowing the absolute values, such as the free and bound proton electromagnetic form factors, as well as the European Muon Collaboration effect to extract the structure function F2 ratio of the bound to free nucleons by the corresponding cross section ratio. We also present the results calculated with the different current quark mass values for the strange and bottom quarks to see the possible impact. Furthermore, for practical use we give the explicit density-dependent parametrizations for the vector potentials of the baryons and light-(u, d) quarks, as well as for the effective masses of the baryons treated in this study, and of the mesons ω, ρ, K, K*, η, $η^{′}$, D, D*, B, and B*.